Judicial Review of the Audi et Alteram Partem Principle in Denpasar Administrative Court Ruling No. 2/G/LH/2018/PTUN.DPS - Nailah Abiliah, Hana; Graciea Firdaus , Raine; Shifaunissa (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
The development of the Celukan Bawang Coal-Fired Power Plant Phase II has generated an environmental dispute that resulted in the Denpasar Administrative Court Decision Number 2/G/LH/2018/PTUN.DPS. This case is significant as it concerns the application of the audi et alteram partem principle, a fundamental principle guaranteeing the right of parties to be heard fairly, particularly in environmental disputes that are preventive in nature and involve broader public interests. This study aims to analyze the application of the audi et alteram partem principle in the decision and to examine its implications for access to justice for affected communities. This research employs a normative legal research method using statutory and conceptual approaches, with secondary legal materials analyzed through qualitative descriptive analysis. The findings show that the panel of judges only fulfilled the formal hearing requirement by allowing the parties to submit their claims, but failed to meet the substantial hearing requirement by not seriously considering empirical evidence and substantive arguments presented by the plaintiffs. The termination of the case at the preliminary stage without examining the merits undermined the precautionary principle and weakened the protection of community environmental rights. In conclusion, the application of the audi et alteram partem principle in this decision was not optimal and resulted in a denial of justice in environmental law enforcement.